The wicked will rise ebook - Paige, Danielle (Dorothy Must Die, 2015)
In this New York Times bestselling sequel to Dorothy Must Die, who is good—and who is actually Wicked? The Wicked Will Rise is perfect for fans of richly reimagined fairy tales and classic tales like Marissa Meyer's Lunar Chronicles and Gregory Maguire's Wicked. My name is Amy Gumm—and I'm the other girl from Kansas. After a tornado swept through my trailer park, I ended up in Oz. But it wasn't like the Oz I knew from books and movies. Dorothy had returned, but she was now a ruthless dictator. Glinda could no longer be called the Good Witch. And the Wicked Witches who were left? They'd joined forces as the Revolutionary Order of the Wicked, and they wanted to recruit me. My mission? Kill Dorothy. Except my job as assassin didn't work out as planned. Dorothy is still alive. The Order has vanished. And the home I couldn't wait to leave behind might be in danger. Somehow, across a twisted and divided land, I have to find the Order, protect the true ruler of Oz, take Dorothy and her henchmen down—and try to figure out what I'm really doing here.